Calibration of resistance factors for design of deep foundations against lateral deflections. (April 2023) - He, Pengpeng; Fenton, Gordon A.; Griffiths, D.V.
Abstract: In geotechnical engineering, the load and resistance factor design (LRFD) approach has been recommended as an alternative to the global factor of safety method. In this paper, the geotechnical resistance factors for the ultimate and serviceability limit states (ULS and SLS) of laterally loaded piles under wind loading are calibrated using a reliability-based method. Both cohesive and frictional soils are considered. Parametric studies are performed to investigate the effects of various parameters on the estimated failure probability, and the required resistance factors for ULS and SLS are provided. The results indicate that the effect of the limiting maximum pile head deflection on the required resistance factor is negligible and that the "worst case" correlation length depends on the pile length. In addition, the required resistance factor for ULS design is 0.55 to 0.78, suggesting that the value of ϕg = 0.50 stipulated by geotechnical code provisions in Canada is relatively conservative. Considering the target lifetime failure probability of 0.01 for SLS, the required resistance factor is around 0.60 for both clay and sand, which is smaller than the recommendation of ϕg = 0.80 by the design codes in Canada.